Research on leading agricultural enterprises guiding farmers' participation in pre-production quality and safety control: evidence from the Yangtze River Delta Region of China - Liu, Chenying; Li, Wen; You, Yulan; Yang, Qizhi; Li, Mingjuan (Frontiers in Sustainable Food Systems, 2025)
The leadership of agricultural enterprises in guiding farmers to participate in pre-production quality and safety control not only helps promote high-quality agricultural development and drives the industrialization process of agriculture, but also provides important support for achieving the goal of building a strong agricultural nation. The re-search employs a grounded theory approach to conduct a multi-case study, following the general logic of “Motivations-Behaviors-Outcomes.” Relevant data from case companies were extracted, analyzed, and coded to construct a theoretical interpretation, revealing the intrinsic mechanisms of agricultural leading enterprises in pre-production quality and safety control and identifying key influencing factors. Additionally, using fuzzy-set qualitative comparative analysis, the study explores how five enterprise control behaviors—village-enterprise cooperation, integration of primary, secondary, and tertiary industries, agricultural mechanization, agricultural digitalization, and agricultural technology promotion—collaborate to guide farmers' involvement in pre-production quality and safety control from a configurational perspective. The results indicate that agricultural leading enterprises guide farmers' participation in pre-production quality and safety control through organizational linkage mechanisms and new quality productive forces elements linkage mechanism, and based on this, six configurational paths are summarized, leading to the identification of three constructs: Industry Integration-driven, Digital Intelligence-driven, and Land Trusteeship-driven. This paper focuses on agricultural leading enterprises and farmers in the Yangtze River Delta region of China. The study does not limit itself to exploring the independent influence of enterprise-led actions in guiding farmers' participation in pre-production quality and safety control, but rather investigates how multiple factors work together to lead farmers' participation under various interacting elements.